Bollywood and Colourism: Exploring the discourse of Blackness in Hindustani cinema - Goolamally, Saadiya (Centre for Film and Media Studies, 2024)
This research paper explores the discourse of blackness with a focus on skin colour in Hindustani cinema. It undertakes a gendered analysis of the representation of skin colour. While this research paper maps the historical background of Colourism in Hindustani cinema which is rooted in Casteism, it also documents and analyses the use of the colour line in the representation of vice and virtue. Eventually, it looks into casting patterns of Hindi film directors with skin colour as a determining factor informing narratives, shaping ideological codes, dictating beauty ideals and perpetuating cinematic dogmas. It also investigates the link between Colourism and race through an exploration of the representation of Afro-identities strongly rooted into mimicry within the microcosmic cultural sphere of Hindustani cinema. Finally, it contends that the representation of the colour line has undergone an aestheticization as a result of the gentrification of Hindustani cinema for the purpose of transnational negotiations. Therefore, I posit my contention within the inextricable dynamics of Colourism, Afro-pessimism and ‘black face' mimicry to proclaim that the colouristic and broadly racist agenda within the discourse of the colour line in Hindustani cinema still persists in Bollywood cinema as the gentrification of Hindustani cinema has generated solely a superficial change.